Single Context Archaeology as Anarchist Praxis - Morgan, Colleen; Eddisford, Daniel (Journal of Contemporary Archaeology, 2019)
The organization of archaeological fieldwork often resembles a military-style campaign structured around rigid, top-down hierarchies. This is reflected in many aspects of current practice, including the ultimate authority of the site director, the use of excavation methodologies that remove the act of interpretation from field archaeologists, and the general deskilling and reification of archaeological labor in fieldwork. Though there have been several examples of resistance to this hierarchical model we maintain that a sustained critique could stem from an unexpected source: the creation of communities that model anarchist principles through the implementation of the single context methodology in archaeology. In this article we explore the potential for anarchist praxis in archaeological fieldwork and the implications of anarchist thought on the issues of authority and non-alienation of labor in a neoliberal landscape.